CONSTRUCTION OF A NEW ELECTROCHEMICAL SENSOR BASED ON A NEW MOLECULARLY IMPRINTED POLYMERS(MIPS) FOR HIGHLY SELECTIVE AND SENSITIVE DETERMINATION OF CLEBOPRIDE (CBD) IN PHARMACEUTICAL COMMERCIAL SAMPLES - Al-Bayati, Y. K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Clebopride (CBD) selective molecularly imprinted polymers(MIPs) were based on ion-pair by prepared four polymers(MIPs) using CBD as the template a well as (Acryl amide) (AAM), 2-Acrylamido-2-Methyl-1-Propane sulphonic Acid (2-AAMMPSA as monomer, used N,N-ethylenebismethacrylamide (EBMAA) ,ethylene glycol dimethacrylate ethylene glycol(EGDMAC), N, N-methylene bisacrylamide (NNMBAAM)) as cross linker and used benzoyl peroxide as initiator . NIPs prepared by using the same composition of MIPs except the template (CBD). The MIPs were prepared using variation  ratio of monomer and cross linker .These MIPs applicate as solid phase extraction for determination CBD in pharmaceutical preparation used UV as detector .the results gave good response, where the reconstruction percentage (Rec%) value of CBD drug took the range (99- 101% ), and the relative standard deviation (RSD%) value took the range (0.27% - 0.93 %) for standard solution and Rec% took values of (98- 99) %, and RSD% took values of (0.86 – 1.62) % of CBD drug for the Clebopride pharmaceutical.